2012
DOI: 10.3389/fimmu.2012.00099
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Development Against Leishmania donovani

Abstract: Visceral leishmaniasis (VL) caused by Leishmania donovani and Leishmania infantum/chagasi represents the second most challenging infectious disease worldwide, leading to nearly 500,000 new cases and 60,000 deaths annually. Zoonotic VL caused by L. infantum is a re-emergent canid zoonoses which represents a complex epidemiological cycle in the New world where domestic dogs serve as a reservoir host responsible for potentially fatal human infection and where dog culling is the only measure for reservoir control.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 295 publications
(272 reference statements)
0
40
0
1
Order By: Relevance
“…For the past 20 years, DNA cloning and characterization of genes encoding parasite proteins suitable for the development of defined vaccines have been carried out [7] . Several native and recombinant antigens, tested in murine models, have shown different degrees of protection [1,[8][9][10][11] . Recombinant Ldccys1 protein elicits protective immune responses in Leishmania chagasi infected BALB/c mice [12] .…”
Section: Introductionmentioning
confidence: 99%
“…For the past 20 years, DNA cloning and characterization of genes encoding parasite proteins suitable for the development of defined vaccines have been carried out [7] . Several native and recombinant antigens, tested in murine models, have shown different degrees of protection [1,[8][9][10][11] . Recombinant Ldccys1 protein elicits protective immune responses in Leishmania chagasi infected BALB/c mice [12] .…”
Section: Introductionmentioning
confidence: 99%
“…he protozoan parasite Leishmania donovani is one of the major causative agents of visceral leishmaniasis (VL), which is the second most challenging infectious disease worldwide, with nearly 500,000 new cases and 60,000 deaths annually (1).…”
mentioning
confidence: 99%
“…Determination of host immune responses showed that resiquimod liposome treatment was associated with enhanced IFN-γ and IL-10 production by splenocytes activated with specific antigen compared with control or carrier-alone groups. These two cytokines act antagonistically as IFN-γ production stimulates macrophages to kill Leishmania and is associated with protection against L. donovani infection whereas IL-10 suppresses macrophage activation and its production is associated with susceptibility [52]. However, the relative local concentration of each cytokine at the site of infection will be important in determining whether the immunostimulatory effects aid parasite clearance or not.…”
Section: Intravenous Deliverymentioning
confidence: 96%